2016
DOI: 10.1007/s00702-016-1558-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the interval-between-sessions on prefrontal transcranial direct current stimulation (tDCS) on cognitive outcomes: a systematic review and meta-analysis

Abstract: Recently, there has been wide interest in the effects of transcranial direct current stimulation (tDCS) of the dorsolateral prefrontal cortex (DLPFC) on cognitive functioning. However, many methodological questions remain unanswered. One of them is whether the time interval between active and sham-controlled stimulation sessions, i.e. the Interval Between Sessions (IBS), influences DLPFC tDCS effects on cognitive functioning.Therefore, a systematic review and meta-analysis was performed of experimental studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 82 publications
(99 reference statements)
4
41
1
2
Order By: Relevance
“…Subjects were removed from the scanner, after which the tDCS surface electrodes (25 cm 2 ) were covered in electrode gel and positioned on the scalp based on each participant's structural scan using the Brainsight neuronavigation system (Brainsight™, Rogue Research, Inc., Montreal, Quebec, Canada). To avoid carry-over tDCS effects, based on our recent meta-analysis (Dedoncker, Brunoni, Baeken, & Vanderhasselt, 2016b), the time interval between the two stimulation sessions (active/sham tDCS) was at least 2 days. The cathodal electrode was placed on the right supraorbital area (1 cm above the eyebrows; Figure 1).…”
Section: Tdcsmentioning
confidence: 99%
“…Subjects were removed from the scanner, after which the tDCS surface electrodes (25 cm 2 ) were covered in electrode gel and positioned on the scalp based on each participant's structural scan using the Brainsight neuronavigation system (Brainsight™, Rogue Research, Inc., Montreal, Quebec, Canada). To avoid carry-over tDCS effects, based on our recent meta-analysis (Dedoncker, Brunoni, Baeken, & Vanderhasselt, 2016b), the time interval between the two stimulation sessions (active/sham tDCS) was at least 2 days. The cathodal electrode was placed on the right supraorbital area (1 cm above the eyebrows; Figure 1).…”
Section: Tdcsmentioning
confidence: 99%
“…While no studies have assessed the impact of estrogen on tDCS induced neuromodulation, two retrospective analyses of TMS data, one cognitive study and a systematic review have examined the impact of gender. Collectively they found that, compared with men, women demonstrated greater changes in motor and visual evoked potential amplitudes, visual phosphine thresholds, and cognition following tDCS, and may be more responsive to right hemisphere stimulation under certain cognitive demands (Chaieb, Antal, & Paulus, ; Dedoncker, Brunoni, Baeken, & Vanderhasselt, ; Kuo, Paulus, & Nitsche, ; Meiron & Lavidor, ). However, all but one of these investigations was retrospective and information regarding menstrual phase, and thus estrogen levels, were not available for analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, only the studies by Dedoncker et al. () and Meiron and Lavidor () examined the dorsolateral prefrontal cortex (DLPFC) tDCS, with Chaieb et al. and Kuo et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that while enhancing effects of anodal tDCS in cognition are consistently reported, the effects of cathodal tDCS are less clear [10,11]. Nevertheless, tDCS has not only become useful for investigating brain function in diverse domains, but is also starting to be used for the treatment of various neuropsychiatric disorders [12].…”
Section: Introductionmentioning
confidence: 99%